2022
DOI: 10.1021/acs.jpclett.1c04080
|View full text |Cite|
|
Sign up to set email alerts
|

Ice Recrystallization Inhibition by Amino Acids: The Curious Case of Alpha- and Beta-Alanine

Abstract: Extremophiles produce macromolecules which inhibit ice recrystallization, but there is increasing interest in discovering and developing small molecules that can modulate ice growth. Realizing their potential requires an understanding of how these molecules function at the atomistic level. Here, we report the discovery that the amino acid l -α-alanine demonstrates ice recrystallization inhibition (IRI) activity, functioning at 100 mM (∼10 mg/mL). We combined experimental assays with mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
(77 reference statements)
1
18
0
Order By: Relevance
“…This confirms that the amine/acid are crucial for activity, which is in agreement with previous computational data for a/balanine, which suggests the amine/acid contacts the growing ice face, rather than the hydrophobic domain. 23 Altogether, the data shown support a hypothesis that facial amphiphilicity is an essential motif in the activity of these amino acids, which agrees with observations of modified glycans 13 and polymers. 18 The small molecule IRI-active agent safranin-O is also facially amphiphilic, but that is not the only reason for its IRI This journal is © The Royal Society of Chemistry 2022 activity.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…This confirms that the amine/acid are crucial for activity, which is in agreement with previous computational data for a/balanine, which suggests the amine/acid contacts the growing ice face, rather than the hydrophobic domain. 23 Altogether, the data shown support a hypothesis that facial amphiphilicity is an essential motif in the activity of these amino acids, which agrees with observations of modified glycans 13 and polymers. 18 The small molecule IRI-active agent safranin-O is also facially amphiphilic, but that is not the only reason for its IRI This journal is © The Royal Society of Chemistry 2022 activity.…”
supporting
confidence: 85%
“…Warren et al recently reported that the amino acid l -α-alanine could slow ice growth, but that the isomeric β-alanine could not. 23 Molecular simulations suggested that this was not due to ice-binding affinity, but rather differences in the compatibility with the ice lattice and ability to become overgrown by the ice. This presents the exciting possibility for the use of amino acids, and their (easily available) derivatives, as scaffolds for minimal ice growth inhibitors.…”
mentioning
confidence: 99%
“…1 Therefore, one of the main avenues of research in cryopreservation is the search for new CPAs. Recent advances include small molecule ice recrystalisation inhibitors, 13 amino acids, 14 and acetamides, 15 however so far success has been limited. 12,[16][17][18] Recent work has demonstrated the synergistic effect of combining nontoxic CPAs to improve outcomes, suggesting that mixtures, rather than single agents, may be the key to improved cryoprotectant solutions.…”
Section: Introductionmentioning
confidence: 99%
“…6 For many translational applications synthetic mimics of proteins are desirable, but must be scalable, durable and tunable. 7,8 Small molecule ice growth inhibitors have been reported [9][10][11][12] as have self-assembled materials, 13,14 bespoke peptides 15,16 and graphenics. 17,18 One of the most active synthetic mimics reported to date is poly(vinyl alcohol) (PVA).…”
Section: Introductionmentioning
confidence: 99%